Pengaruh Gaya Kepemimpinan, Motivasi Kerja, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta - Sari, Enyka Cummalla, Ihwan Susila. SE, M.Si, Ph.D (2017)
This study aims to look at the influence of leadership style, employee motivation, and work environment on employee performance Faculty of Economics and Business, University of Muhammadiyah Surakarta. The sample in this study were 48 respondents working in the faculty of economics and Business University of Muhammadiyah Surakarta. The analysis technique used to use validity, reliability testing, regression analysis. The findings menunjukkaan that partially and simultaneously leadership style, employee motivation, and work environment positive and significant effect on employee performance. Of the three variables tested were able to explain the variable performance of employees amounted to 38.1% and the rest is influenced by other variables of 61.9%